Abortion Indications According to Law Number 17 of 2023 concerning Health: Indikasi Aborsi Menurut UU No. 17 Tahun 2023 tentang Kesehatan - Siregar, Rospita Adelina (Universitas Muhammadiyah Sidoarjo, 2024)
This normative juridical research scrutinizes Indonesia's legal framework surrounding abortion, juxtaposing the criminalization of abortion with the nuanced provisions of Law Number 17 of 2023 concerning health. The study focuses on Article 42, which permits abortion under specific indications such as fetal viability challenges and pregnancies resulting from rape. The primary legal materials are sourced from statutory regulations, with a supplementary examination of secondary legal materials. The research reveals the legal complexities surrounding abortion in Indonesia, shedding light on the delicate balance between criminal sanctions and legal protections. The implications of the findings extend to the broader discourse on reproductive rights and the evolving legal landscape. Highlights: Abortion Legislation in Indonesia: Balancing criminal sanctions and legal protections under Health Law Number 17 of 2023. Indications and Protections: Analyzing specific indications like fetal viability challenges and rape pregnancies, shaping women's reproductive rights. Normative Juridical Research: Utilizing primary and secondary legal materials to navigate the intricate legal landscape surrounding abortion in Indonesia. Keywords: Abortion, Planning, Legal Protection